Thai Sugar-Sweetened Beverage Tax: Does It Really Help? - Suriya, Sitaporn; Torut, Buraskorn (Kesmas, 2025)
A solution recommended by the World Health Organization to prevent and control noncommunicable diseases is the Sugar-Sweetened Beverage (SSB) tax. This study aimed to evaluate the Thai SSB tax efficiency affecting the change in post-tax individual-level consumption and find causal explanations for the people’s consumption behavior after the SSB tax was implemented. This study used a Productivity Model, and stratified random sampling was conducted by selecting 1,200 people. An in-depth interview was conducted to seek causal explanations for post-SSB tax consumption behavior with 15 key informants. The results revealed the SSB tax’s efficiency in terms of perception and understanding at 6.75% and in terms of awareness and compliance at 2.83%. Several reasons for the failure of such a policy included no price differences for products with and without sugar, lack of coverage in regulatory enforcement, addiction to sweet tastes, insufficient food literacy, and the dangers of artificial sweeteners. Therefore, a careful and comprehensive review and revision of the tax implementation is necessary. The integration of complementary policy instruments alongside the tax is also required.